K. Marx: man and society - Sidorenko, Irina N.; Saiganova, Veronika S.; Liahchylin, Anatoly A. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article is devoted to the disclosure of life and scientific work, as well as the analysis of the main socio-philosophical ideas of the great German thinker K. Marx, who had set the main vectors of intellectual thought in the XX – early XXI centuries. The main accent in the article is made on the disclosure and comprehension of the role and place of man in society, the problem of his alienation and ways to resolve it. It is stated that the position of the modern man was entirely subordinated to the regulations that lead to alienation and dehumanisation – the obligatory attributes of capitalist society. For the authors of this article it seems not only possible, but also expedient to turn to the creative heritage of K. Marx in order to show the relevance and significance of philosophical and sociopolitical ideas, to reveal the reasons for the renaissance of Marxist philosophy in the modern world, and to note the legitimacy of readjustment of the Marxist intellectual framework for understanding modern global capitalism and total alienation.